FOREWORD OFFICIAL OPENING VI FRANCO LATINO AMERICAN FORUM ON BIOETHICS. SAN JOSE COSTA RICA, 2-3 MAY 2019 - Christian BYK (Journal international de bioéthique et d’éthique des sciences, 2022)
Excellency Don Daniel Salas, Minister of Health of Costa Rica, Mr. Rector of the University of Costa Rica, Excellency Dona Esther Kuisch-Laroche, Director and Representative of the UNESCO Office in San José, Excellency Mr. Thierry Vankerk-Hoven, Ambassador of France in Costa Rica, Distinguished Prof. Alfonso Chacon Mata, Chairman of the Scientific Committee of the Forum, Distinguished Ladies and Gentlemen, Those of you who have known me for some time will say how much I like to illustrate in these opening words what is for me the concrete meaning of our meetings. Even absent, I will not miss this ritual and this time I will rely on the personality and work of the writer and woman of Costa Rican culture Carmen Naranjo. Indeed, how to respond with relevance to this simple question: what brings us together today in a continuity of reflection and cooperation? As Chair of UNESCO’s Intergovernmental Bioethics Committee and Secretary-General of the International Association of Law, Ethics and Science, I could confidently insist on the indispensable international dimension of the struggle to make bioethics and sustainable development the tools of a more equitable world, more solidarity and concern for future generations. With the words of Carmen Naranjo, I choose to tell you in a more direct and stronger way that “Everything that strengthens knowledge must be implemented, hence the importance of spreading universities and develop what communities have (and for that reason), it is not necessary to take out people from their place of origin, but rather to reach them and succeed in starting the spiral of development…